2009
DOI: 10.1111/j.1439-0272.1996.tb02775.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of interferon-gamma in seminal plasma of infertile men

Abstract: The role of the cell-mediated immunity in male infertility is still far from clear. Interferon-gamma (INF-y), a secretory product of activated T cells and natural killer cells, has been hypothesized to have a toxic effect on sperm function. The presence of INF-y was investigated in seminal plasma of fertile and infertile subjects, using a specific enzyme-linked immunosorbent assay, in order to study its role in male infertility. Forty-one subjects were studied; 20 had proven fertility and normal semen quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…In our study, it was possible to detect IFN‐γ in all the seminal plasma samples collected. This is in agreement with the data presented by others (Paradisi et al. , 1996).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, it was possible to detect IFN‐γ in all the seminal plasma samples collected. This is in agreement with the data presented by others (Paradisi et al. , 1996).…”
Section: Discussionsupporting
confidence: 94%
“…The previous research has shown no significant difference in IFN‐γ levels between fertile and infertile subjects. However, increased IFN‐γ concentrations in the seminal plasma of infertile subjects have also been found (Paradisi et al. , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Paradisi et al . () have shown that IFN‐γ secretion is increased in the infertile men. Zhang et al .…”
Section: Discussionmentioning
confidence: 98%
“…For instance, high concentrations of IFN-c, IL-17, MCP-1, MDC, IL-6 and IL-8 had been measured in SP samples from infertile men or having pathological processes in their genital tract. [17][18][19]27,28 Some other SP cytokines, such as IL-10, had shown contradictory results among studies. Huleihel et al (1999) reported lower concentrations of IL-10 in infertile than fertile men, whereas Miller et al (2002) reported opposite results.…”
Section: Discussionmentioning
confidence: 99%